COGNITIVE NEUROSCIENCE AND INCLUSIVE PRACTICES IN MATHEMATICS TEACHING - de Menezes, Vinicius Iuri; da Silva, Lucas de Morais; de Camargo, Éder Pires; Capellini, Vera Lucia Messias Fialho; dos Reis, Verônica Lima (Seven Editora, 2024)
This study examines the role of cognitive neuroscience in promoting inclusive practices in mathematics teaching, offering an approach that considers the diverse needs of students. With advances in neuroscience, there is a deeper understanding of processes such as working memory, attention, and visuospatial skills, which are essential for learning mathematics. These processes are key to creating inclusive teaching environments, especially for students with specific educational needs, such as Autism Spectrum Disorder (ASD), Attention Deficit Hyperactivity Disorder (ADHD), and Dyslexia. Exploratory and descriptive documentary research aimed to explore the intersection between cognitive neuroscience and inclusive practices in mathematics teaching, showing how these approaches can promote more accessible, equitable, and effective learning for all students, especially those who need differentiated support. Although the implementation of these practices faces challenges, such as the need for continuous teacher training, the benefits found are substantial. The publications and examples of practical implementation demonstrate how integrating cognitive neuroscience into inclusive mathematics teaching can improve student performance and motivation. It is observed that this integration not only makes mathematics education more accessible, but also contributes to a more equitable and meaningful education for all students. DOI:https://doi.org/10.56238/sevened2024.037-064